Diffuse Large B-Cell Lymphoma in a 36-Year-Old Patient: Case Report - Sousa Lima, Mariana; Paim, Neiva Pereira; Alegranci, Pâmela (Brazilian Journal of Case Reports, 2026)
Non-Hodgkin lymphomas (NHL) are a diverse group of clonal lymphoid tumors characterized by an irregular pattern of dissemination. The incidence of NHL has increased over the past 50 years, currently affecting approximately 17 per 100,000 individuals. Among the different subtypes, diffuse large B-cell lymphoma (DLBCL) is the most common and is most frequent in older patients. A 36-year-old man reported recurrent sinusitis, almost three times a year. The patient presented with a cervical nodule, followed by the rapid emergence of an oropharyngeal mass. Approximately one month after the onset of symptoms, the diagnosis was confirmed as bulky stage IIIBE, C-MYC positive Diffuse Large B-Cell Lymphoma (DLBCL). Despite being classified as high risk, the patient had a favorable prognosis and achieved complete remission following treatment, which included chemotherapy (R-CHOP) and radiotherapy, underscoring the effectiveness of standardized treatment protocols even in highly aggressive presentations.